Discourse on the philosophical and ethical method of Aristotle. Karbowski, J. (2019). Aristotle’s Method in Ethics: Philosophy in Practice. Cambridge, UK; New York: Cambridge University Press. - Butsykina, Yevheniia (Sententiae, 2022)
Review of Karbowski, J. (2019). Aristotle’s Method in Ethics: Philosophy in Practice. Cambridge University Press.